BOOK REVIEW SOPHIE KINSELLA’S CONFESSION OF A SHOPAHOLIC - Nurhayati, Devy (LANTERN (Journal on English Language, Culture and Literature), 2017)
Women are always interested in making themselves look good. Looking good here means not only physically, but also characteristically. They need self actualization in their association. Mostly, women who are older than 25 years old and have already had good jobs choose to live in urban areas. The obsession of trying various things automatically increases. The things are, for example, social relationship, urban lifestyle, and shopping activities. When women are somehow in a situation where they receive their paychecks and suddenly some advertisements show a fifty percent discount for all items whose deadline last in a week, a very triggering question emerges: what are they going to do? This is a very tough query, particularly for those who have problem in differentiating between actual necessities and temporary desires.